Military Expenditure And Economic Growth In SAARC Countries - Zaheer, Rummana; Gilani, Sidrah; Siddiqui, Armughan Nafees (Advances in Social Sciences Research Journal, 2017)
To keep a sufficient defense system, it is a dire need in today’s world to spend a good amount of national income on the defense and military to maintain security and sovereignty of the country. This paper aims to study the growth performance of four of the eight South Asian Association for Regional Corporation (SAARC) nations, that are Pakistan, India, Bangladesh and Sri Lanka, with special emphasis on the impact of military and defense expenditure on the economic growth of each country. The data consists of 31 years (1985-2015) time series of the selected dependent and explanatory variables of all the above mentioned countries. The objective of this study is to shed the light on both, theoretical as well as empirical evidence about the share of some of the important factors in the economy and to analyze the impact of a huge share of defense expenditures on the economic growth of a nation. The author’s results indicate that military expenditure has a negative impact on economic growth in India and Pakistan, while in case of Bangladesh and Sri Lanka estimates suggest a positive impact of military expenditure and economic growth in both of the countries.